Sound Perturbations, Visual Resonances: Reflections About Sound in Three Experimental Films (2018)
This article analyzes the imaginaries and sound spaces in three recent Chilean films produced by Diluvio productions: Lucía (Atallah 2010), Rey (Atallah 2017), and La casa lobo (Cociña & León 2018). Based on these films, we will study the diverse uses of sound as a strategic device to re-signify both the narrative proposals as well as the audiovisual material used. The films studied share certain aspects of a fictional cinema of realistic typologies, as understood by some realist theorists, together with the subjective and expressive representation of the experimental and expanded cinema. We propose a reading of the work from the hinge between the cinematographic and the visual arts, pausing at the different practices of each work, in order to expose and contrast the different uses of sound that are tensing the ways of working the noises, the silence, the off camera, the sound of expression materials and the construction and destruction of the sound and the plastic.